Tissue factor cytoplasmic tail regulates myeloid cell derived superoxide formation and TGF-beta 1 driven cardiac remodeling in myocardial infarction. (25th November 2020) - Garlapati, V.S; Molitor, M; Efentakis, P; Lagrange, J; Wild, J; Karbach, S; Vujacic-Mirski, K; Muenzel, T; Daiber, A; Brandt, M; Kossmann, S; Milting, H; et al.
Abstract: Background: In the setting of myocardial infarction (MI), patients with coronary no-reflow and/or delayed presentation after onset of symptoms (sub-acute MI) are inflicted by severe thrombo-inflammation and are marked by worse clinical outcome. However, it is unclear whether tissue factor (TF) contributes to outcome post MI solely by the regulatory functions of its cytoplasmic tail independently of its coagulation activity. Purpose: We analyzed the role of the TF cytoplasmic domain in the recruitment of myeloid cells into the infarcted myocardium and the consequences on cardiac remodeling, scar formation, development of heart failure and survival post MI. Methods: Twelve Patients enrolled in the MICAT (Mainzer Intracoronary Database, ClinicalTrials.gov Identifier: NCT02180178) study were examined. Patients with sub-acute MI and stable coronary artery disease were defined and monocytes were isolated from peripheral blood mononuclear cells (PBMCs). Human heart samples acquired from the left ventricular wall of explanted hearts following cardiac transplantation or obtained during implantation of left ventricular assist device. Samples were investigated for downstream analysis of protein by western blots, RNA quantification and cryo-sectioning. MI was induced in 9 to 12 weeks old male C57BL/6J mice, mice specifically lacking the cytoplasmic tail (CT) of TF (TFΔCT mice) and TFfl/flLysMCre+/− mice by permanent ligation of the left anterior descending artery. Left ventricular function was assessed by High-Frequency Ultrasound System. Infiltration of immune cells into the infarcted myocardium was analyzed by performing flow cytometric analysis after enzymatic digestion of the myocardium. Superoxide levels were quantified by HPLC-based measurement of dihydroethidium derived oxidation product 2-hydroxy ethidium. Results: Circulating monocytes in patients with sub-acute MI showed increased nitrosative stress as well as increased phosphorylation of TF CT along with TGF-β1 and NF-kB inflammatory activation, which was recapitulated in cardiac tissue of end-stage heart failure patients with chronic MI. MI results in phosphorylation of the CT of TF within myeloid cells. Using mice with conditional knockout of TF on myeloid cells or TFΔCT mice, we found that this regulatory intracellular domain of TF within myeloid cells is required for cardiac infiltration of inflammatory Ly6Chigh TF+ monocytes, Rac-1 GTPase and superoxide formation of gp91phox + myeloid cells in MI. TGF-β1 dependent SMAD2 activation and cardiac collagen deposition as late sequel of MI was reduced in TFΔCT mice, resulting in attenuated cardiac dysfunction and reduced mortality. Conclusion: We conclude that, TF CT drives NADPH-oxidase derived superoxide formation, thrombo-inflammation and cardiac fibrosis. Therefore, it might serve as putative biomarker and risk predictor in MI Funding Acknowledgement: Type of funding source: None